Run Gauntlets or Pay Pirates? Regulating Vessel Speeds in High-Risk Waters - McDowell, Ryan W. (American Journal of Trade and Policy, 2021)
Maritime commerce in world commerce. Each year, vessels carry more cargo at higher costs and faster speeds. Insurance is an integral part of shipping, as it protects cargoes and crews against the perils of the sea. This article focuses on the peril of piracy, a criminal practice that has evolved significantly throughout history. Pirates today, as pirates of the past, prey upon the unprotected. Yet, modern piracy, unlike historical piracy, is essentially non-violent. The modern pirate profits from ransom, not theft. Today, piracy is a monetary risk with computable consequences: an insurable threat. Anti-piracy methods, including insurance, impose steep costs to world trade. In the past decade, pirate activity has declined while piracy insurance has grown more expensive. This phenomenon is problematic, but an industry-wide solution is a challenging construct. To handle the costly risks of piracy is to balance the distinct and competing interests of ship-owners, insurers, operators, and governments. As this Article argues, insurance can more efficiently mitigate piracy’s puzzling risk. After discussing maritime piracy and maritime insurance, this Article outlines the legal and regulatory schema for a system to mandate the speeds of vessels that transit pirate-prone waters. The proposed regulation is mechanically sound, logistically feasible, cost-effective, and enforceable. To diminish the costly risk of piracy, this Article proposes revising a treaty to afford the International Maritime Organization (IMO) jurisdiction to regulate vessel speeds on the high seas.